Effect of Potassium on Growth, Fruit Quality Improvements and Resistance to Anthracnose in Field Grown Capsicum (Capsicum Annum L. Cv. ‘Hungarian Yellow Wax’) - Somapala, K.S.; Weerahewa, H.L.D.; Thrikawala, S. (My University, 2016)
Postharvest losses of capsicum crop accounts for 30-40% of total crop production. It has been shown that postharvest losses of capsicums can be reduced significantly with the application of potassium due to improvements in disease resistance and fruit quality. The objective of this study was to investigate the effect of higher doses of potassium (K) on plant growth, yield and fruit quality parameters and resistance to anthracnose disease of capsicum cv. ‘Hungarian Yellow wax’. Three different levels of potassium, Department of Agriculture (DOA) recommended level [180g per bed (control)], double the level (360g per bed) and three times of the level (540g per bed) were applied to the soil in a Randomized Complete Block design. The same experiment was repeated in three farmer fields of Naula Grama Niladhari (GN) division in Dambulla Divisional Secretariat of Matale district of the central province of Sri Lanka. Plant growth parameters were measured at two week intervals, and fruit quality parameters (TSS, Ph, %TA), fruit physical parameters (length, width, pericarp thickness, fresh weight, firmness and cell wall thickness) were recorded. Finally the resistance to diseases of capsicum fruits was also tested by inoculation of Colletotrichum capsici to the fruits. This study concludes that application of higher doses of potassium improves some plant growth parameters (height and plant diameter at base), fruit physical parameters (fruit length, width , fresh weight, firmness and cell wall thickness). The tripled and doubled the dose of potassium application reduced anthracnose disease by over 75% and 95% respectively indicating that higher level of K could have a significant impact in reducing postharvest losses of capsicum in local conditions
Keywords: Potassium application; capsicum anthracnose; fruit quality